Sepsis Management in Post Exploratory Laparotomy due to Total Bowel Obstruction and Gaster Perforation: A Case Report - Noor, Efry Sofyan; Maulydia, Maulydia; Kusuma, Edward (Journal of Neonatal Surgery, 2025)
Background: Sepsis remains a leading cause of mortality worldwide despite the advancement of intensive care, particularly in low- and middle-income countries (LMICs) where resources are limited. Early recognition as well as timely and intensive management is necessary to lower the mortality. This case report aimed to highlight the critical role of early sepsis detection and timely management in successful outcomes, even in resource-constrained environments. Case Report: We reported a case of 64-year-old woman presented with chief complaints of not being able to defecate and has not passed gas for 5 days, accompanied with stomach ache, bloating, and mucus in the stool. The patient was diagnosed with total bowel obstruction due to suspect intussusception, sepsis, hyponatremia hypovolemic and acute kidney injury. An exploration laparotomy with right hemicolectomy and end-to-end anastomose procedures were then performed. Blood culture showed Escherichia coli and Extended Spectrum b-Lactamase (ESBL) while urine culture showed Candida tropicalis. Intensive management comprised of resuscitation, antibiotics and antifungal treatment lead to improvement within eight days of admission. The patient was discharged fourteen days after surgery. Conclusion: The successful outcome of this case highlights the importance of early recognition and aggressive management of sepsis, especially in resource-limited environments.